2022
DOI: 10.21203/rs.3.rs-1678627/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innovation of NURBS feedrate direct interpolator in five-axis for CNC high-precision and high-efficiency machining

Abstract: The high-precision machining is restricted by truncation error and computational burden of second-order derivative in the second-order Taylor expansion (STE) interpolator which is usually used by scholars due to its advantages of high-precision and G3 continuity or higher. In conventional methods, the improved accuracy of interpolation parameter in the Taylor expansion interpolator will lead to a great increase in the computational burden of higher-order derivatives or compensation methods, resulting in degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Wang et al [3] introduced the pre-compensation-based theory to increase machining precision by lowering contour errors while maintaining federate. Cao et al [4] suggested a feedrate direct interpolator (FDI), which can effectively acquire potentially precise interpolation parameters without using rounding or compensation techniques. Li et al [5] employed the Sigmoid function for feedrate planning, considering both geometric and kinematic errors.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [3] introduced the pre-compensation-based theory to increase machining precision by lowering contour errors while maintaining federate. Cao et al [4] suggested a feedrate direct interpolator (FDI), which can effectively acquire potentially precise interpolation parameters without using rounding or compensation techniques. Li et al [5] employed the Sigmoid function for feedrate planning, considering both geometric and kinematic errors.…”
Section: Introductionmentioning
confidence: 99%